Estudo numérico dos conectores Crestbond em pilares mistos esbeltos - Ariany Cardoso Pereira (2020)
Concrete-filled steel tube (CFST) columns cross section can be classified according to the local slenderness of the steel tubular profile as slender, semi-compact or compact. Although the analytical models determine the axial resistance force, there is still little research and solutions available about the force transfer mechanisms between CFST columns and beams. This study aims to present the development and validation of a numerical model to simulate the behavior of Crestbond connectors applied to slender CFST columns. For this purpose, experiments were carried out to expand the database used for the validation and application of a numerical model developed in previous works. After defining the numerical model, which can be used for the study and design for force transfer in slender columns with sheet metal connectors, known as composite dowels, a sensitivity study of the most relevant parameters was carried out. Finally, it was found that the slenderness of section governed the connection's behavior, regardless of the parameters being evaluated, and that the geometric and mechanical characteristics of the connector are fundamental points to be observed in the definition of a most efficient shear connector for application in concrete filled stel tube columns.